Tradisi Jawa Pengaruhnya Terhadap Orang Kristen dan Tinjauan Dari Sudut Pandang Alkitab - Jois Efendi; Harming Harming; Katarina Katarina (Skenoo : Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
Humans are social beings who live in the community, in society there are cultural values ​​that bind to unite them. In it there are traditions that must be carried out. Javanese traditions influence on Christians and views from a biblical point of view. The method used is descriptive qualitative which aims to introduce Javanese tradition and see it from a biblical point of view. As a result, the Javanese still use tradition, and tradition is attached to the life of the Javanese, re-examining traditions with Bible truth. Because the tradition is man-made to honor his ancestors, while the Bible says: "God who made the earth and all that is in it, He who is Lord of heaven and earth, does not live in temples made by human hands" (Acts 17:24). ).